Effective implementation of risk/principles based approach in a supervisory authority - Huertas, Thomas (Henry Stewart Talks, 2009)
Supervision is part of a broader tapestry, Building a consistent framework, Does monetary policy crank the asset cycle?, A troubled environment, Business models pose challenges, Senior management is responsible for assuring compliance with principles and rules, Capital and liquidity, Valuation processes require improvement, The control environment needs strengthening
Archived at 2025/05/28